Une exploration de la recherche scientifique sur la transformation digitale dans le champ disciplinaire de l'économie : Une étude bibliométrique de 2015 à 2024 - JANATI-IDRISSI , Farid; TGHALI, Amal (Revue Internationale du Chercheur, 2025)
Abstract This article examines scientific publications concerning digital transformation (DT) from 2015 to 2024 in the field of economics, using the Scopus database and software packages VOSviewer and R. At the start of the procedure, we identified a total of 29,977 articles, however, only 1660 are selected for the study. The analysis focuses on journals, articles, researchers, institutions and countries, using bibliometric indicators such as productivity, citations, H-index values. Mapping analyses highlights co-citation, co-authorship, word frequency, research topics and influential researchers. This analysis aims to unveil the intellectual structures and accumulated knowledge in the existing literature while analyzing the emerging trends that encourage researchers to deepen their scientific investigations. The results complement each other and show that China, Germany, Ukraine and Spain are the most productive countries for DT research.